Faktor-Faktor yang Mempengaruhi Pertumbuhan Ekonomi di Kabupaten Tabanan - Putra, I Komang Trisna Eka; Yasmita, I Gusti Ayu Lia; Marta, I Nyoman Gede (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2024)
This study aims to determine the influence of direct expenditure, Budget Surplus (SILPA), and local levies on economic growth in Tabanan Regency, from 2013 to 2022. The variables in this study are economic growth in Tabanan Regency as the dependent variable and direct expenditure, Budget Surplus (SILPA), and local levies as independent variables. The data used in this study are secondary data obtained from the Tabanan Regency Central Statistics Agency (BPS). The analysis method employed is multiple linear regression. The results of the analysis lead to the conclusion that: the direct expenditure variable (X1) has a significant and positive influence on economic growth in Tabanan Regency, the Budget Surplus (SILPA) variable has a significant and positive influence on economic growth in Tabanan Regency, and the local levies variable has a significant and positive influence on economic growth in Tabanan Regency. Simultaneously, it is found that the direct expenditure, Budget Surplus (SILPA), and local levies variables collectively have a significant influence on economic growth in Tabanan Regency.